Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 3 - Differentiation - 3.8 Implicit Differentiation - Exercises - Page 152: 1


$$2x+6y^2\frac{dy}{dx}=0.$$ $$\frac{dy}{dx}=-\frac{x}{3y^2}.$$ $$\frac{dy}{dx}|_{(2,1)}=-\frac{2}{3}.$$

Work Step by Step

Differentiating the equation $ x^2+2y^3=6$ with respect to $ x $ and using the chain rule, we get $$2x+6y^2\frac{dy}{dx}=0.$$ Hence, $$\frac{dy}{dx}=-\frac{x}{3y^2}.$$ Moreover, we have $$\frac{dy}{dx}|_{(2,1)}=-\frac{2}{3}.$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.